Identification of Telomere-Related Gene Signatures for Immune Cell Infiltration and Prognosis in Hepatocellular Carcinoma - Sun, Juntao; Gao, Ye; Xu, Ruotong; Fu, Hao; Ying, Xinyi; Yan, An; Ling, Sunbin (Translational Cancer Research, 2026)
Hepatocellular carcinoma (HCC) is a common malignancy with poor clinical outcomes. Telomere maintenance is crucial for tumor cell proliferation, yet the role of telomere-related genes (TRGs) in HCC prognosis remains unclear.